Calculation of P,T-odd interaction constant of PbF using Z-vector method in the relativistic coupled-cluster framework - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2015)
The effective electric field experienced by the unpaired electron in the ground state of PbF, which is a potential candidate in the search of electron electric dipole moment due to some special characteristics, is calculated using Z-vector method in the coupled cluster single-and double-excitation approximation with four component Dirac spinor. This is an important quantity to set the upper bound limit of the electron electric dipole moment. Further, we have calculated molecular dipole moment and parallel magnetic hyperfine structure constant (A(parallel to)) of Pb-207 in PbF to test the accuracy of the wavefunction obtained in the Z-vector method. The outcome of our calculations clearly suggests that the core electrons have significant contribution to the ``atom in compound'' properties. (C) 2015 AIP Publishing LLC.

Calculation of hyperfine structure constants of small molecules using Z-vector method in the relativistic coupled-cluster framework - Sasmal, Sudip; Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Sciences, 2016)
The Z-vector method in the relativistic coupled-cluster framework is employed to calculate the parallel and perpendicular components of the magnetic hyperfine structure constant of a few small alkaline earth hydrides (BeH, MgH, and CaH) and fluorides (MgF and CaF). We have compared our Z-vector results with the values calculated by the extended coupled-cluster (ECC) method reported in Phys. Rev. A 91 022512 (2015). All these results are compared with the available experimental values. The Z-vector results are found to be in better agreement with the experimental values than those of the ECC values.

Correlation trends in the magnetic hyperfine structure of atoms: a relativistic coupled-cluster case study - Talukdar, Kaushik; Sasmal, Sudip; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2018)
The role of electron correlation in the hyperfine structure of alkali metals and alkaline earth metal monopositive ions in their ground electronic configuration is investigated using the Z-vector method in a relativistic coupled-cluster regime within the singles and doubles approximation. The systematic effects of core-correlating functions, polarization of core electrons, and high-lying virtual functions on core electrons correlation are studied. The study reveals that the core-correlating function plays a significant role in core polarization and thus is very important for precise calculation of the wave function near the nuclear region. The inner-core electrons (1s-2p) require very high virtual energy functions for proper correlation. Therefore, the all-electron correlation treatment and the inclusion of higher-energy virtual functions are the key factors for precise calculation of the hyperfine structure constant of atoms. Our calculated values are in excellent agreement with the available experimental values, which also implies that the wave function produced by the Z-vector method is accurate enough for further calculation of the parity- and time-reversal symmetry-violating properties in atoms and molecules.